2020
DOI: 10.1002/bio.3981
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐enhanced Cs4PbBr6/CsPbBr3 composites films synthesized by double‐films solid phase reaction method

Abstract: Due to indispensable ligands, polluted organic solution, or complex vapour deposition, stable CsPbBr3 film is hard to be prepared directly using a simple and environmentally friendly method. To improve the stability of CsPbBr3 film and its synthesis methods, the double‐films solid phase reaction was developed, and Cs4PbBr6/CsPbBr3 composites were designed. Although the synthesized particle had a size of 2–5 μm, much larger than that of quantum dots, in ambient conditions the composites films still showed good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Several research groups have demonstrated possible luminescence mechanisms for the intense green PL from Cs 4 PbBr 6 , which include (i) emission from CsPbBr 3 NCs (as impurities, inclusions, or CsPbBr 3 /Cs 4 PbBr 6 interfaces) and (ii) defect-induced emission (such as Br vacancies, interstitial hydroxyl, polybromide, and self-trapped excitation). [22][23][24][25][26][27][28][29][30] The absence of traces related to CsPbBr 3 NC impurities in the X-ray diffraction (XRD) pattern, transmission electron microscopy (TEM) images, and scanning electron microscopy (SEM) images has prompted concerns regarding the accuracy of the former theory. Although the latter theory is supported by density functional theory (DFT) simulations, it faces the problem of reproducing the calculated deep-level defect states through other DFT simulations and rarely agrees with the experimental results obtained for lead halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have demonstrated possible luminescence mechanisms for the intense green PL from Cs 4 PbBr 6 , which include (i) emission from CsPbBr 3 NCs (as impurities, inclusions, or CsPbBr 3 /Cs 4 PbBr 6 interfaces) and (ii) defect-induced emission (such as Br vacancies, interstitial hydroxyl, polybromide, and self-trapped excitation). [22][23][24][25][26][27][28][29][30] The absence of traces related to CsPbBr 3 NC impurities in the X-ray diffraction (XRD) pattern, transmission electron microscopy (TEM) images, and scanning electron microscopy (SEM) images has prompted concerns regarding the accuracy of the former theory. Although the latter theory is supported by density functional theory (DFT) simulations, it faces the problem of reproducing the calculated deep-level defect states through other DFT simulations and rarely agrees with the experimental results obtained for lead halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely a consequence of the gradual decomposition of Cs 4 PbBr 6 into CsPbBr 3 and CsBr under the inuence of ambient humidity, relevant to the reaction process Cs 4 PbBr 6 / CsPbBr 3 + 3CsBr. During this process, the decomposed CsPbBr 3 grains and the Cs 4 PbBr 6 internal CsPbBr 3 grains continue to fuse and grow, and the crystallinity tends to be complete, 41,42 eventually leading to enhanced uorescence. This is also consistent with the conclusion obtained from PL spectra.…”
Section: Effect Of Air-annealing Temperature On the Cspbbr 3 -Cs 4 Pb...mentioning
confidence: 99%
“…19 Akkerman et al, 20 introduced the Cs 4 PbBr 6 phase and embedded nanocrystals of CsPbBr 3 in the photoactive Cs 4 PbBr 6 forming a Cs 4 -PbBr 6 /CsPbBr 3 core-shell structure, electrons and holes formed in CsPbBr 3 are spatially conned by Cs 4 PbBr 6 , which can signicantly improve the luminescence efficiency. 21 The 0-D Cs 4 PbBr 6 phase of CsPbBr 3 , known for its lattice matching provides ideal passivation and efficient exciton connement, has served as an inspiration for our research. This has led us to introduce the Cs 4 PbBr 6 phase to prepare CsPbBr 3 -Cs 4 PbBr 6 composite lms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation